Peningkatan Ketahanan Kayu Palapi (Heritiera simplicifolia(Mast.) Kosterm) Terhadap Serangan Rayap Kayu Kering (Cryptotermers cynocephalus Light) Melalui Perendaman dalam Larutan Biotermikill 100EC dan Ekstrak Kulit Kayu Eboni - Asni, Asni (Universitas Tadulako, 2019)
The present research aimed to evaluate the effect of different types and concentration of wood presertivative to the retention value and wood durability against drywood termite. The preesvative agents used were Biotermikill 100 EC and Ebony woodbark extract. Moisture content and density of wood samples were measured by SNI 03-6848-2002. Retention values were calculated based on the ratio of the treated and underated-wood weight and their volumes in a usual way. Wood durability against drywood termite was determined by comparison of the weight loss of the treated to that underated-wood. The results displayed the highest retention value of Biotermikill EC and Ebony woodbark extract were 0,628kg/m³ dan 0,535 kg/m³ at 3% concentration. In the antitermite assays, both preservatives exhibited the lowest wood weight loos were 0,096% and 0,083% at 3% concentration. The present research displayed that the retention valuse and weight loss of Palapi wood were strongly affected by the concentration of the presrvatives. The results also showed that the concentration of preservatives used gave slightly better effect to improve Palapi woods durability.Keywords: Concentration of Preservatives, Retention, Biotermikill EC, Ebony Woodbark Extract.